Analisis return on investment: Edukasi literasi keuangan pemasaran digital bagi UMKM Cakebytri di Kota Palembang - Meilinda Dwi Anugrah; Ulfah Tika Saputri; Edy Firza; Zulkifli Zulkifli; Siska Aprianti (Nur Science Institute, 2026)
This community service activity aimed to improve digital marketing and financial literacy among Cakebytri MSMEs in Palembang City by applying Return on Investment (ROI) analysis. The activity was carried out in three stages: preparation, education, and evaluation, using interactive materials on digital marketing and ROI calculation simulations based on simple data and actual business data. The results showed an improvement in participants’ understanding, as indicated by an increase in the average pre-test score from 60 to 85 in the post-test, representing a 41.67% improvement. Participants were also able to calculate and interpret ROI independently. The analysis showed that all advertising platforms generated positive ROI, with TikTok Ads as the most optimal platform, followed by Instagram Ads and Facebook Ads. As a follow-up, the partner was encouraged to use a simple recording format and evaluate ROI regularly at the end of each digital advertising period. This activity contributes to strengthening financial literacy, improving the efficiency of marketing budgets, and supporting data-driven decision-making for business sustainability.